Study on the fabrication and mechanical characterization of graphene-epoxy nanocomposite material - Md. Nazmus, Sakib (2022)
Excessive use of automobiles causes environmental issues and greenhouse gas emissions. Researchers and producers try to overcome the challenges of environmental safety by producing fuel-efficient, weight minimized automobiles with the help of lightweight polymer composite materials instead of heavy materials. Epoxy as a thermoset polymer added with proper filler material produces nanocomposite material, which increased mechanical, chemical, electrical, and thermal properties, high compatibility, low cost, and shrinkage played significant roles in this regard. Among other filler materials, Graphene, the thinnest two-dimensional atomic material, has immerged as a revolutionary material and sparked a flurry of research and innovation, is preferred due to its outstanding properties and high specific surface area. Graphene nanofiller modified epoxy nanocomposite is currently subject to intense research due to its lightweight and potential in a wide range of structural and functional applications. The polymer composite's overall performance largely depends on the volume/weight percentage of the reinforcement fillers' homogenous dispersion and a strong affinity between the filler and the polymer matrix. Graphene-Epoxy and Graphene-Epoxy-SDS nanocomposite have been made with three different wt.% (0.3, 0.5, 1) of Graphene Oxide (GO) by solution mixing technique. Sodium Dodecyl Sulphate (SDS) has been used as a surfactant for homogenous dispersing graphene in the epoxy matrix to overcome strong van der Waals force and re-aggregation graphene. Graphene Oxide (GO) and SDS were dispersed in acetone by sonication, and epoxy resin was added. After removing the acetone and adding a hardener, the mixture was poured into silicon molds, and then the nanocomposite was cured overnight in a vacuum oven. The prepared nanocomposites and GO Powder were characterized by Transmission electron microscopy (TEM), Scanning Electron Microscope (SEM), Energy Dispersive X-Ray (EDX), X-ray Diffractometer XRD), and Fourier-Transform Infrared Spectroscopy (FTIR). To investigate the effect of filler loading on mechanical properties hardness, tensile and flexure tests were done. Graphene-Epoxy nanocomposite, 0.5 wt.% of GO filler loading showed (11%) higher hardness, whereas 1wt.% of GO filler exhibited 7.4% higher tensile and 8.33% flexure strength compare to pure epoxy. Graphene-Epoxy-SDS nanocomposite was synthesized with constant SDS loading with three different wt% (0.3, 0.5, 1) of GO. It enhanced that 0.5wt.% GO-Epoxy-SDS nanocomposite have exhibited the highest mechanical properties, which are 24.1% hardness, 40.74% tensile, and 37.01% flexure strength increment than the epoxy matrix. So 0.5wt% of graphene loading is recommended as optimum loading in this study of the epoxy matrix, and SDS surfactant demonstrated higher properties. This study would be helpful to use in lightweight structural applications, especially in automobile and aircraft parts.